2015
DOI: 10.1097/iop.0000000000000356
|View full text |Cite
|
Sign up to set email alerts
|

Compressive Optic Neuropathy and Repeat Orbital Decompression

Abstract: Purpose To characterize the presenting characteristics, pre-operative clinical activity score (CAS), surgical approach, and visual outcomes in patients with thyroid eye disease undergoing repeat orbital decompression for recurrent or recalcitrant compressive optic neuropathy. Methods The medical records of patients with recurrent or recalcitrant compressive optic neuropathy (CON) undergoing repeat orbital decompressions were retrospectively reviewed. The primary outcome measures included pre- and post-operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 38 publications
0
14
0
3
Order By: Relevance
“… 8 Despite the widespread use of these modalities over decades for TED, the literature is mostly comprised of retrospective studies, Case reports and small case series which now guide practice patterns in the treatment of DON. 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 There has only been one prospective, randomized controlled trial (RCT) to compare corticosteroids versus corticosteroids and surgical decompression for DON. 12 In this study, Wakelkamp et al reported similar initial outcomes after medical decompression and surgical decompression, and found that immediate surgical decompression did not result in better visual outcomes nor did it preclude the use of corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Despite the widespread use of these modalities over decades for TED, the literature is mostly comprised of retrospective studies, Case reports and small case series which now guide practice patterns in the treatment of DON. 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 There has only been one prospective, randomized controlled trial (RCT) to compare corticosteroids versus corticosteroids and surgical decompression for DON. 12 In this study, Wakelkamp et al reported similar initial outcomes after medical decompression and surgical decompression, and found that immediate surgical decompression did not result in better visual outcomes nor did it preclude the use of corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…VF defects occur as concordance with the localization of the lesion. [1][2][3][4][5][6]18,[28][29][30] Stage 0 papilledema Papilledema is optic disc swelling due to elevated intracranial pressure. Optic nerve damage develops due to intraneuronal ischemia secondary to the stasis in the axoplasmic flow.…”
Section: Compressive Optic Neuropathymentioning
confidence: 99%
“…A variety of treatment strategies have been described for DON including oral or intravenous (IV) corticosteroids, surgical decompression, and orbital radiation. 10,[28][29][30][31] Most current treatment strategies initially use high-dose corticosteroids as a first-line therapy for optic neuropathy and reserve decompression surgery for persistent defects. Orbital radiation is occasionally used as an adjunct to corticosteroids.…”
Section: Optic Neuropathymentioning
confidence: 99%